Protein intake from different sources and cognitive decline over 9 years in community-dwelling older adults - Gao, Rongtao; Yang, Zhan; Yan, Wenju; Du, Weiping; Zhou, Yuan; Zhu, Feng (Frontiers in Public Health, 2022)
Objectives To examine the association of protein intake from different sources with cognitive decline. Methods Our analysis included 3,083 participants aged 55–93 years from the China Health and Nutrition Survey. Cognition was assessed in 1997, 2000, 2004, 2006, and 2015. Diet intake was assessed using weighing methods in combination with 24-h dietary recalls for three consecutive days at each survey. Results Participants consumed 13.94% of energy intake from total protein, with 11.47 and 2.47% from plant and animal sources, respectively. During a follow-up of 9 years, participants in quintile 5 of plant protein intake (% energy) had a higher risk [odds ratio (95% CI): 3.03 (1.22–7.53)] of cognitive decline compared with those in quintile 1. Higher animal protein intake (% total protein) was associated with a lower risk of cognitive decline [odds ratio (95% CI) for quintile 5 vs. quintile 1: 0.22 (0.07–0.71)]. Grains (plant source) protein intake was inversely but fish/shrimp and poultry (animal source) protein intake were positively associated with change in cognitive Z-score. Conclusion Increasing animal protein consumption in a population with plant dominant diets may help to prevent cognitive decline.